HNF4α Acts as Upstream Functional Regulator of Intestinal Wnt3 and Paneth Cell FateSummary - Christine Jones; Mariano Avino; Véronique Giroux; Francois Boudreau (Cellular and Molecular Gastroenterology and Hepatology, 2023)
Background & Aims: The intestinal epithelium intrinsically renews itself ex vivo via the proliferation of Lgr5+ intestinal stem cells, which is sustained by the establishment of an epithelial stem cell niche. Differentiated Paneth cells are the main source of epithelial-derived niche factor supplies and produce Wnt3 as an essential factor in supporting Lgr5+ stem cell activity in the absence of redundant mesenchymal Wnts. Maturation of Paneth cells depends on canonical Wnt signaling, but few transcriptional regulators have been identified to this end. The role of HNF4α in intestinal epithelial cell differentiation is considered redundant with its paralog HNF4γ. However, it is unclear whether HNF4α alone controls intrinsic intestinal epithelial cell growth and fate in the absence of a mesenchymal niche. Methods: We used transcriptomic analyses to dissect the role of HNF4α in the maintenance of jejunal epithelial culture when cultured ex vivo as enteroids in the presence or absence of compensatory mesenchymal cells. Results: HNF4α plays a crucial role in supporting the growth and survival of jejunal enteroids. Transcriptomic analyses revealed an autonomous function of HNF4α in Wnt3 transcriptional regulation and Paneth cell differentiation. We showed that Wnt3a supplementation or co-culture with intestinal subepithelial mesenchymal cells reversed cell death and transcriptional changes caused by the deletion of Hnf4a in jejunal enteroids. Conclusions: Our results support the intrinsic epithelial role of HNF4α in regulating Paneth cell homeostasis and intestinal epithelium renewal in the absence of compensatory Wnt signaling.